Yen Loans to Malaysia: Impact on Five Year Plans from 1969 to 2010 - Mohd Huda, Mohd Ikbal; Hassan, Asmadi; Ibrahim, Sulatan (WILAYAH: The International Journal of East Asian Studies, 2013)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.